Development and psychometric evaluation of the sexual knowledge and attitudes scale for premarital couples (SKAS-PC): An exploratory mixed method study - Zohreh Sadat; Fazlollah Ghofranipour; Seyed Ali Azin; Ali Montazeri; Azita Goshtasebi; Azam Bagheri; Elham Barati (Shahid Sadoughi University of Medical Sciences, 2018)
Background: Designing a valid and reliable questionnaire that allows a fair evaluation of sexual knowledge and attitudes and develop a proper sexual educational program is necessary. Objective: The present study was designed to develop and psychometric evaluation of the sexual knowledge and attitudes scale for premarital couples. Materials and Methods: An exploratory mixed method study was conducted in two phases; in the first, in order to develop a questionnaire an item pool was generated on sexual knowledge and attitudes through focus group discussions and individual interviews. In the second phase, the psychometric properties of the questionnaire were examined. For this purpose, face validity, content validity as well as construct validity were conducted. Reliability was assessed by the Cronbach’s alpha coefficient to assess internal consistency and test-retest reliability. Results: In the first phase an item pool with 88 questions was generated (sexual knowledge 45 items and sexual attitudes 43 items). In the second phase, the number of final items reduced to 33 and 34 items of sexual knowledge and sexual attitudes respectively, through exploratory factor analysis (EFA). Five factors for sexual knowledge and six factors for sexual attitudes identified by EFA. The Cronbach’s alpha coefficient for two sections was 0.84 and 0.81 respectively. The test- retest correlations for sexual knowledge and sexual attitude was 0.74 and 0.82 respectively. Conclusion: The findings suggest that the Sexual Knowledge and Attitudes Scale for Premarital Couples is a valid and reliable instrument. Further studies are needed to establish stronger psychometric properties for the questionnaire.